Colocating an accredited practising dietitian to an adult community mental health service: An exploratory study. (27th April 2018) - Furness, Trentham; Wallace, Elizabeth; McElhinney, Jo; McKenna, Brian; Cuzzillo, Celeste; Foster, Kim
Abstract: For people with severe mental illness, accredited practising dietitians may assist with a nutrition care plan that considers the medical, psychiatric, psychological, social, spiritual, and pharmacological aspects of their care. However, consumers' access to care has been limited by difficulties attending appointments and suboptimal interface between nutritional and mental health services. Therefore, the objectives of this exploratory study were to describe access to, and key stakeholder perspectives of, the accredited practising dietitian role colocated in a community mental health service. A total of 16 key stakeholders participated in one‐to‐one interviews. Two main themes with subthemes were derived from analysis of interviews: (i) 'building empowerment and collaboration' and included the subthemes, (a) nutrition awareness and education and (b) healthy lifestyle changes, and (ii) 'overcoming challenges to optimal nutrition and effective health care'. In addition, improved access to the role was demonstrated with 124 (79%) consumers attending at least one appointment with an accredited practising dietitian. A total of 15 (12%) consumers attended more than 10 appointments during their outpatient admission to the community mental health service. Colocating an accredited practising dietitian was perceived to build empowerment and collaboration, and overcome challenges to optimal nutrition and effective health care for consumers, carers, and clinicians. The colocation of a dietitian can empower consumers' to make health‐informed decisions and support their willingness to engage with physical healthcare provision when it is prioritized alongside mental healthcare provision.